Religious Freedom and Constitutional State - Abad Yupanqui, Samuel (2008)
The present paper analyzes the relationship Church-State in Peru, the diverse debates provoked with respect to this question and the necessity to develop legal norms that support the religious freedom. In this sense, the author develops, in the first place, the models that influenced the drafting of the different constitutions throughout Peruvian history. These, in relation to the State-Church relationship, move away from the French and North American model, and in contrast to these, they follow the line of the Spanish model. The author emphasizes the 1979 Constitution, which represents a change in the model followed by his predecessors, and in the Agreement signed by the Peruvian State with the Catholic Church in 1980. Second, it describes the model adopted in the Constitution of 1993, which is inspired, basically, in the Constitution of 1979. It also analyzes the debates arising from a proposal in the constitutional reform project, after the fall of Alberto Fujimori's regime. One of the main debates originated with respect to the possible modification of Article 71 of the Constitution, in which it was stated that the Peruvian State recognized and respected the different religious confessions, in addition, this had to establish collaboration agreements with them, with equity. On the other hand, the author indicates which are the principles that should guide the Church-State relationship: i) freedom and religious equality, ii) the principle of neutrality, secularity or non-confessionality and iii) cooperation or collaboration within the framework of the secularism of the State. Finally, the possibility and necessity of a law that develops these principles and that supports religious freedom in Peru is developed. The Bill of Law 1008-2006-CR is deeply analyzed, which includes the proposal formulated by the Working Table constituted by Ministerial Resolution No. 070-2005-JUS.